O efeito crônico do treinamento aeróbico e do exercicío aerobíco máximo sobre o estresse oxidativo e a capacidade antioxidante em homens treinados e sedentários - Camilo Oliveira Geraldi (2019)
Oxidative stress is a condition that occurs when the imbalance between oxidation from energy metabolism and its compensation through the antioxidant defense system, in favor of the increased expression of reactive oxygen species (ROS) and nitrogen (RN) species. The relationship between ROS formation and antioxidant capacity is called the redox balance. Chronic oxidative stress can cause cellular damage through oxidation and inflammation, and is associated with the development of numerous diseases. Acute oxidative stress is associated with fatigue during exercise. On the other hand, studies have demonstrated that ROS can act favoring adaptations to physical exercise, or even favoring the fight against an inflammatory process. This study aims to evaluate the effects of the level of aerobic conditioning on indicators of oxidative stress and antioxidant capacity indicators, in rest situation, and after a progressive exercise to exhaustion (VO2max test). Participants in this study were highly trained subjects (n = 14, VO2max = 62.5 ml/ kg/ min ± 6.07) and sedentary subjects (n = 14, VO2max = 33.3 ml/ kg / min ± 3.69), all of them male, between the ages of 18 and 40 years. Before and after exercise, serum levels of antioxidant capacity (superoxide dismutase (SOD), reduced glutathione (GSH), oxidized glutathione (GSSG) and glutathione ratio (GSH/ GSSG)) and oxidative stress (thiobarbituric acid reactive substances (TBARS), nitric oxide (NO)) to estimate the redox balance and the cumulative action of antioxidants which cooperate in the removal of reactive oxygen species in tissues and body fluids. Independently of the moment, TBARS concentrations were higher and the antioxidant activity was lower (GSH / GSSG higher) for the sedentary group. After the progressive exercise until exhaustion, for the sedentary, there was an increase in TBARS, NO, GSH/ GSSG and SOD concentrations. For the trained group, there was an increase in TBARS and SOD concentrations, and NO reduction. The results indicate that aerobically trained adults have reduced oxidative stress and increased antioxidant capacity. A session of progressive exercise to exhaustion provides increased oxidative stress independently of the state of aerobic conditioning.